The microstructure of di-alkyl chain cationic/nonionic surfactant mixtures: observation of coexisting lamellar and micellar phases and depletion induced phase separation. - Penfold, J; Staples, E; Ugazio, S; Tucker, I; Soubiran, L; Hubbard, J; Noro, M; O'Malley, B; Ferrante, A; Ford, G; Buron, H (2005)
The evolution of the microstructure and composition occurring in the aqueous solutions of di-alkyl chain cationic/nonionic surfactant mixtures has been studied in detail using small angle neutron scattering, SANS. For all the systems studied we observe an evolution from a predominantly lamellar phase, for solutions rich in di-alkyl chain cationic surfactant, to mixed cationic/nonionic micelles, for solutions rich in the nonionic surfactant. At intermediate solution compositions there is a region of coexistence of lamellar and micellar phases, where the relative amounts change with solution composition. A number of different di-alkyl chain cationic surfactants, DHDAB, 2HT, DHTAC, DHTA methyl sulfate, and DISDA methyl sulfate, and nonionic surfactants, C12E12 and C12E23, are investigated. For these systems the differences in phase behavior is discussed, and for the mixture DHDAB/C12E12 a direct comparison with theoretical predictions of phase behavior is made. It is shown that the phase separation that can occur in these mixed systems is induced by a depletion force arising from the micellar component, and that the size and volume fraction of the micelles are critical factors.